Epidemiological characteristics of imported acute infectious diseases in Guangzhou, China, 2005-2019 - Wen-Hui Liu; Chen Shi; Ying Lu; Lei Luo; Chun-Quan Ou (Public Library of Science (PLoS), 2022)
Background The global spread of infectious diseases is currently a prominent threat to public health, with the accelerating pace of globalization and frequent international personnel intercourse. The present study examined the epidemiological characteristics of overseas imported cases of acute infectious diseases in Guangzhou, China. Methods We retrospectively investigated the distribution of diseases, demographic characteristics, and temporal and spatial variations of imported cases of acute infectious diseases in Guangzhou based on the surveillance data of notifiable infectious diseases from 2005 to 2019, provided by Guangzhou center for Disease Control and Prevention. The Cochran-Armitage trend test was applied to examine the trend in the number of imported cases over time. Results A total of 1,025 overseas imported cases of acute infectious diseases were identified during the study period. The top three diseases were dengue (67.12%), malaria (12.39%), and influenza A (H1N1) pdm09 (4.10%). Imported cases were predominantly males, with a sex ratio of 2.6: 1 and 75.22% of the cases were those aged 20-49 years. Businessmen, workers, students and unemployed persons accounted for a large proportion of the cases (68.49%) and many of the cases came from Southeast Asia (59.02%). The number of imported cases of acute infectious diseases increased during the study period and hit 318 in 2019. A clear seasonal pattern was observed in the number of imported cases with a peak period between June and November. Imported cases were reported in all of the 11 districts in Guangzhou and the central districts were more seriously affected compared with other districts. Conclusions The burden of dengue imported from overseas was substantial and increasing in Guangzhou, China, with the peak period from June to November. Dengue was the most common imported disease. Most imported cases were males aged 20-49 years and businessmen. Further efforts, such as strengthening surveillance of imported cases, paying close attention to the epidemics in hotspots, and improving the ability to detect the imported cases from overseas, are warranted to control infectious diseases especially in the center of the city with a higher population density highly affected by imported cases. Author summary Guangzhou, a city located in the south of China, is heavily affected by imported infectious disease, with frequent trade, personnel movements and unique subtropical monsoon climate which favors transmissions of various infectious diseases. In this study, we examined the epidemiological characteristics of imported cases of acute infectious diseases in Guangzhou, 2005-2019. Our findings highlighted the potential risk of spread of infectious diseases triggered by imported cases. The top three imported acute infectious diseases were dengue, malaria and influenza A (H1N1)pdm09 and most of the imported cases came from Southeast Asian. The burden of dengue imported from overseas was substantial and increasing in Guangzhou, China, with the peak period from June to November. Most imported cases were males aged 20-49 years and businessmen. Further efforts, such as strengthening surveillance of imported cases, paying close attention to the epidemics in hotspots, and improving the ability to detect the imported cases from overseas, are warranted to control infectious diseases especially in the center of the city with a higher population density highly affected by imported cases.